Effect of chemical component characteristics of waste cooking oil on physicochemical properties of aging asphalt. (15th August 2022) - Zhao, Yuechao; Chen, Meizhu; Zhang, Xintao; Wu, Shaopeng; Zhou, Xinxing; Jiang, Qi
Highlights: The method for classification of waste cooking oil (WCO) components was proposed. The physicochemical properties of different components of WCO were investigated. The effect of different components of WCO on the physical and chemical properties of aging asphalt were studied. The rejuvenation effect of different components of WCO on aging asphalt is mainly determined by their own characteristics. Abstract: The combined utilization of waste cooking oil (WCO) and reclaimed asphalt pavement (RAP) is attractive for economic, environmental, and energy benefits. However, the quality stability of WCO is poor due to its wide sources, which limits the further development of WCO recycled RAP. In this study, the classification method of WCO was proposed according to the molecular weight difference of its chemical components, and WCO was classified into three categories including light components (LC), intermediate components (IC), and heavy components (HC). Meanwhile, the characteristics of these three WCO components and their effects on the physicochemical properties of aging asphalt were investigated comprehensively. The experimental results show that the softening ability of different components of WCO on aging asphalt is mainly determined by their molecular weight and thermal stability. Furthermore, LC rich in methyl palmitate is easy solidification and volume expansion at the low temperature, which is not conducive to the repair of low-temperature ductility of aged asphalt. The chemical property analyses of recycled asphalt indicate that there is no chemical reaction between the components of WCO and the aging asphalt. The physical dilution ability of WCO components on carbonyl index, sulfoxide index, and high molecular weight substances of aging asphalt is positively correlated with their molecular weight. In addition, HC contains chemical substances similar in composition to asphalt, which has the most obvious effect on the colloidal structure of aging asphalt. Overall, the classification method for WCO and related findings found in this study provides a reference for ensuring the quality stability of WCO and its industrial application in the recycling of aged asphalt.